1982
DOI: 10.1017/s0022172400070777
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the growth of Vibrio cholerae biotype eltor and biotype classical in foods

Abstract: The growth of Vibrio cholerae biotype eltor and biotype classical was studied in a range of cooked foods, shellfish and raw vegetables, incubated at 22 degrees, 30 degrees and 37 degrees C. Both biotypes grew in all cooked foods but growth was not demonstrated on raw shellfish. The organism multiplied on some vegetables to levels of the order of 10(6)/g. The classical biotypes of V. cholerae showed a longer lag period than the eltor biotype in some foods particularly when incubated at 22 degrees C. The eltor b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
2

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 9 publications
(9 reference statements)
3
27
0
2
Order By: Relevance
“…Contamination of drinking water was lower than that of foods but like other studies (10) it increased during the rainy season. It was observed that foods eaten after 4 (12). Similar results have been obtained in The Gambia where supplementary foods given to children were heavily contaminated with bacteria, particularly if they were allowed to stand after being prepared (13)(14).…”
Section: Discussionsupporting
confidence: 75%
“…Contamination of drinking water was lower than that of foods but like other studies (10) it increased during the rainy season. It was observed that foods eaten after 4 (12). Similar results have been obtained in The Gambia where supplementary foods given to children were heavily contaminated with bacteria, particularly if they were allowed to stand after being prepared (13)(14).…”
Section: Discussionsupporting
confidence: 75%
“…A negative association between waterborne transmission and desiccation resistance does exist among Shigella sp. [6] and between el tor and classical V. cholerae [26,301,302]. These associations, however, are also consistent with the cultural vectors hypothesis, because contact transmission, desiccation resistance, and benignness should favour each other evolutionarily.…”
Section: The Overall Trend and Alternative Hypothesessupporting
confidence: 71%
“…In spite of the fact that clinical symptoms caused by V. cholerae El are less severe than those caused by V. cholerae Cl , V. cholerae El appears to have outcompeted V. cholerae Cl during the current pandemic (26). It has been proposed that this occurred because of the increased environmental fitness of V. cholerae El (23), the differential susceptibility to lytic phages between the biotypes (47), or the ability of V. cholerae El to more productively utilize carbohydrates such as chitin, which V. cholerae metabolizes when associated with zooplankton in the environment (33,54).…”
Section: Discussionmentioning
confidence: 94%